Understanding Brand Evangelism and the Dimensions Involved in a Consumer Becoming Brand Evangelist - Lina Anggraini (Faculty of Economics, Universitas Sriwijaya, 2018)
Smartphone market is rapidly changing and facing a highly competitive environment, with constant product introductions. It is characterized by quickly evolving technology and designs, aggressive pricing, short product life cycles, and rapid imitation. Thus, the players in smartphone industry need to invent a major breakthrough in their marketing strategy. Consider a large company like Apple. Apple loyalists are some of the most recognized product evangelists in the market, sharing their experiences with emerging technology in enthusiastic ways. Apple as the pioneer of Brand Evangelism in 1984, the company relies on customers to communicate marketing messages to other potential customers. It can be an alternative marketing tool for organizations that want to achieve their sustainable competitiveness as brand evangelists will deliver positive information, ideas, and feelings toward a specific brand to others voluntarily in order to influence consumption behaviour. This study aims to examine the phenomenon of brand evangelism and understand the dimensions involved in a consumer becoming brand evangelist. The research method of this study is based on the implementation of quantitative survey research design. The data used in this study were obtained by administering online questionnaires to 468 respondents who have used Apple iPhone for at least 6 months in Indonesia. The data analysis method used in this study is multiple regression analysis. The findings show that brand satisfaction, consumer-brand identification, brand salience, brand trust and opinion leadership have positive influence towards brand evangelism.